State of the art of resilience, social support and subjective welfare in university students of Huánuco - Ayala-Albites, Flor M. (2019)
This research wants to explain the relationship between resilience, family social support and psychological wellfare in students with few economic resources who enter at "Hermilio Valdizán" National University; these categories in study are essential for optimal mental health development within an evolutionary stage in search of a life project. This descriptivecorrelational study, includes students of the fourteen faculties. The sample was determined with 435 students users of the university dining room with the condition of low economic resources. The concept of subjective wellfare is closely linked to quality of life, which for being multidimensional covers a variety of áreas such as perception of the physical, mental and social wellfare, feelings of satisfaction and gratificaron associated with health, family, economic situation, educational opportunities, self-esteem, creativity and confidence in others. The goal is to ensure and protect the formation of the future professional, who will be responsible for the production of goods and services to society; study the professional potential of young people would mean a great help for the development of legitímate aspirations, search for wellfare and/or the increasein quality of life.